Earthquake response of elastic SDF systems with non-linear fluid viscous dampers. - Lin, Wen-Hsiung (Earthquake engineering & structural dynamics.)
The steady forced and earthquake responses of SDF systems with a non-linear fluid viscous damper (FVD) are investigated. The energy dissipation capacity of the FVD is characterized by the supplemental damping ratio sd and its non linearity by a parameter designated x. It is found that the structural response is most effectively investigated in terms of sd and x because (1) these two parameters are dimensionless and independent and (2) the structural response varies linearly with the excitation intensity. Damper non-linearity has essentially no influence on the peak response of systems in the velocity sensitive spectral region, but differences up to 14 percent were observed in the other spectral regions. The structural deformation is reduced by up to 25 percent when sd = 5 percent; and by up to 60 percent when sd = 30 percent. Non-linear FVDs are advantageous because they achieve essentially the same reduction in system responses but with a significantly reduced damper force. For practical applications, a procedure is presented to estimate the design values of structural deformation and forces for a system with non linear FVD directly from the design spectrum. It is demonstrated that the earthquake induced force in a non linear FVD can be estimated from the damper force in a corresponding system with linear FVD, its peak deformation and peak relative velocity; however, the relative velocity should not be approximated by the pseudo velocity as this approximatiion introduces a large error in the damper force. Finally, a procedure is presented to determine the non linear damper properties necessary to limit the structural deformation to some design value or the structural capacity for a given design spectrum.